Effectiveness of massive transfusion protocol activation in pre-hospital setting for major trauma. Issue 5 (May 2022) - Botteri, Marco; Celi, Simone; Perone, Giovanna; Prati, Enrica; Bera, Paola; Villa, Guido Francesco; Mare, Claudio; Sechi, Giuseppe Maria; Zoli, Alberto; Fagoni, Nazzareno
Highlights: The pre-hospital MTP activation is useful to identify patients that require blood products on arrival at the Emergency Department. The pre-hospital MTP activation increases the number of patients transfused within one hour of admission at the Emergency Department. A Shock Index >0.9 identifies patients that require a higher amount of blood products. Abstract: Introduction: Hemorrhage in major trauma is life-threatening and the activation of the Massive Transfusion Protocol (MTP) was found to reduce the time to transfusion and mortality. The purpose was (i) to verify whether MTP activation identifies patients that require massive transfusions once admitted to the Emergency Department (ED), (ii) to establish whether pre-hospital MTP activation reduces the time to transfusion on arrival at the ED, (iii) to identify the variable that best predicts MTP activation. Materials and methods: This is a retrospective, single-center study. The MTP was implemented at the end of 2012; it was activated for major trauma in pre-hospital setting on the basis on established criteria. Pre-hospital MTP activation aimed to make blood products available prior to the patients' arrival at the ED. The blood products are transfused when the patient arrives at the hospital. Results: The MTP was activated in pre-hospital setting in 219 patients. On arrival at the hospital, the Trauma Team Leader confirmed MTP activation in 146 (66.7%) patients. Patients with MTP criteria received a higher amount of blood products than the patients without MTP criteria, median 7 (IQR 2–13) units versus 2 (0–6) units, respectively ( P  < 0.001). At the same time, patients with a Shock Index ≥ 0.9 received more transfusions (5.5 [2–13] units) compared with patients characterized by a lower SI (2 [0–7.25] units, P  = 0.009). 146 patients were transfused in the first hour of ED admission. Poisson's multiple regression shows that the SI is the variable that better predicted MTP activation compared to age, gender and the number of injured sites. Conclusions: Pre-hospital MTP activation is useful to identify patients that require an urgent blood transfusion on arrival at the ED. Further analysis should be considered to evaluate the implementation of the Shock Index as a criterion to activate MTP.